PENTINGNYA LINGKUNGAN KAYA LITERASI TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Savira Ananda Fitria; Sari Yustiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy is one of the main solutions to overcome problems with the learning motivation of students in elementary schools in the 21st century. Because basically literacy is the main step to develop skills and insights in students. Therefore, the researcher aims to deepen and understand how to implement a text-rich environment in every public and private elementary school in PPL schools to motivate students' learning. This case study research uses qualitative descriptive. This study involved 5 partner schools that became PPL venues, consisting of public and private schools located in the Semarang City and Demak Regency areas. The data collection technique uses interviews, observations and questionnaires. The results of the study show that literacy facilities in elementary schools vary, with literacy activities that increase students' motivation to learn. The role of teachers is very important in creating a supportive literacy atmosphere, which has a positive impact on motivation and academic achievement, although external factors also influence.